2017
DOI: 10.21817/ijet/2017/v9i1/170901410
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Steaming and Steam Explosion on Mechanical Properties of Snake Fruit (Salacca) Fiber

Abstract: Abstract-Application of natural fiber needs treatments, such as chemical, physical and mechanical treatments. The aim of these treatments is for getting purer, cleaner and smaller size cellulose fiber. This paper describes the treatment of Snake Fruit frond fiber using alkali, steaming and steam explosion and investigates the effects on mechanical properties. The single fiber was firstly subjected to alkali treatments with 2%-8% NaOH for 2 -8 hours to room temperature and steaming in 1 -2 bar. The tensile test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…Hemicellulose is one of the easiest lignocellulose materials to degrade via alkali treatment, because the structure contains more amorphous regions compared to crystalline regions (Cai et al 2015). This study was comparable with the report by Darmanto et al (2017), where a 74.9% hemicellulose content was reported after a 3% alkali treatment. Other studies showed a 5% NaOH treatment on Borassus fiber yielded a 3.02% hemicellulose content (Boopathi et al 2012), while a 5% NaOH treatment on banyan roots led to a 10.7% reduction in the hemicellulose content (Ganapathy et al 2019).…”
Section: Chemical Properties Of the Modified Fibrovascular Bundles (Fvb)supporting
confidence: 89%
See 4 more Smart Citations
“…Hemicellulose is one of the easiest lignocellulose materials to degrade via alkali treatment, because the structure contains more amorphous regions compared to crystalline regions (Cai et al 2015). This study was comparable with the report by Darmanto et al (2017), where a 74.9% hemicellulose content was reported after a 3% alkali treatment. Other studies showed a 5% NaOH treatment on Borassus fiber yielded a 3.02% hemicellulose content (Boopathi et al 2012), while a 5% NaOH treatment on banyan roots led to a 10.7% reduction in the hemicellulose content (Ganapathy et al 2019).…”
Section: Chemical Properties Of the Modified Fibrovascular Bundles (Fvb)supporting
confidence: 89%
“…In this study, the percentage increase in the αcellulose content after the NaOH + Na2SO3 treatment was higher compared to previous studies. Furthermore, the NaOH + Na2SO3 treatment was more effective in maintaining the α-cellulose, hemicellulose, and lignin contents, compared to previous studies using S. zalacca as a raw material with a higher concentration and high energy steam treatment (Darmanto et al 2017).…”
Section: Chemical Properties Of the Modified Fibrovascular Bundles (Fvb)mentioning
confidence: 59%
See 3 more Smart Citations